Feminisme Kultural dan Peran Perempuan dalam Deradikalisasi di Indonesia - Christin Rajagukguk; Shary Charlotte Pattipelohy (Journal of International Relations Diponegoro, 2018)
Terrorism is the result of a radical behaviour where radical understanding can trigger a person to take a violent action to achieve their goals. In Indonesia, radical groups have emerged for a long time, even in the past times there have been terrorist attack. The Indonesian government has established the National Agency for Combating Terrorism (BNPT) as a form of commitment in combating terrorism. BNPT itself has a deradicalization program, where the meaning of deradicalization is an attempt to quit the radical notion of radical adherents or terrorist in non-violent ways. Terrorism has long been regarded as the exclusive scope of men, but it has changed now where women are also involved in terrorism, therefore BNPT involved women role in deradicalization in Indonesia. This research use qualitative research method to explains the role of women in BNPT’s deradicalization in Indonesia. To answer this issue is by using cultural feminism theory, finally it has found that the reason’s BNPT involved women role in deradicalization is as a strategy because women had a female essence which is softer, more compasionate and persuasive is able to approach the wives of terrorist, the prisoners and the ex-prisoners. Beside being a strategy, the reason of the BNPT involving women in deradicalization is to regard the aspects and needs of prisoner since the role of family is also needed in the process of deradicalization.